Accumulation of periodic‐acid Schiff granules is increased in the presence of humanized amyloid beta. (December 2021) - Forner, Stefania; Javonillo, Dominic I; Tran, Kristine M; Phan, Jimmy; Da Cunha, Celia; Baglietto‐Vargas, David; Kawauchi, Shimako; Tenner, Andrea J; LaFerla, Frank; MacGregor, Grant R; Green, Kim N; ,
Abstract: Background: Most Alzheimer's disease (AD) cases are sporadic and late‐onset, yet nearly all existing mouse AD models harbor pathogenic mutations, rendering them better representations of familial autosomal‐dominant forms of the disease. As a foundational step to model late‐onset AD (LOAD), we generated and analyzed knock‐in mice that express wildtype human amyloid beta (hAβ‐KI) under control of the mouse App locus in exon 14 flanked by loxP sites (FL). Method: Using a conformation‐specific OC protofibril antibody, we performed immunofluorescence stains on coronal brain slices and quantified the appearance of Periodic Acid‐Shiff (PAS) granules using confocal microscopy. To correlate the appearance of PAS granules with hAβ expression, we crossed hAβ‐KI‐FL mice with UBC‐Cre ERT2 mice to enable Tamoxifen‐inducible cre recombinase‐mediated inactivation of hAβ expression. Finally, we generated hAβ‐KI; PS1 M146V mice to investigate whether co‐expression of familial‐linked AD mutations affect the hAβ‐induced presence of PAS granules. Result: Changing 3 amino acids in the mouse Aβ sequence to its wild‐type human counterpart produced age‐dependent accumulation of PAS granules in the hippocampus of hAβ‐KI mice by 10 months of age. Additionally, we observed impairments in cognition and synaptic plasticity in hAβ‐KI mice. Remarkably, ablating hAβ expression using inducible cre reduced the formation of PAS granules and rescues cognition. Co‐expression of familial‐linked AD mutations with hAβ exacerbated the accumulation of PAS granules compared to homozygous hAβ‐KI and WT mice. Conclusion: Substituting mouse Aβ with the wild‐type human isoform produces significant accumulation of PAS granules and impairments in cognition and synaptic plasticity, highlighting its usefulness in investigating risk factors of LOAD.